Inteligencia para la alimentación, alimentación para la inteligencia. - Prospero-García, Osear; Díaz, Mónica Méndez; Capuleño, Ilia Alvarado; Morales, Marcel Pérez; Juárez, Jehú López; Ruiz Contreras, Alejandra E. (Salud Mental)
Eating is a behavior oriented to get the energy necessary for the organism to survive and to contend with the demands of its environment. Food, besides of energy, provides structure and function, as amino acids are converted into structural or secretion proteins or enzymes. These proteins are synthesized following a strict genetic code. Variants in the genome happen frequently, but only those changes that result in a poor adaptive phenotype are well documented. There are other changes that may go unnoticed due to culture influence, and they may be seen as adaptive because they seem to favor individuals in the short-term. A child that overeats and becomes overweighed is culturally appreciated as a healthy child. However, systematic studies have shown that these feeding styles influenced by culture, in the long-term, result on an irreversible damage to the individual. Food selection also depends on the functioning of homeostatic and hedonistic systems. The homeostatic system involves the hypothalamus that includes nuclei that promote both appetite and satiety. The hedonic system is constituted by the ventral tegmental area and the nucleus accumbens. Stimulation of the ventral tegmental area induces the release of dopamine into the nucleus accumbens, making the individual to experience pleasure. This system also interacts with the hypothalamic systems that promote appetite. As it can be seen, food intake is regulated by diverse cerebral systems that are under the influence of one another. Failure in one of these systems may lead the subject to a compulsive, or defective, food intake. We have allowed media and mercantilist interests to govern our diet, instead of allowing our brain and its systems to do it. We should have psycoeducation as a priority in medicine to improve our capacity to select better quality food to eat, without compromising the pleasure of eating.